Peran Komisi Yudisial dalam Menegakkan Kode Etik Hakim: Analisis Kasus Hakim DA - Rasji; Charisse Evania Tansir; Silvia Evelyn; Rafael Christian Djaja (Jurnal Hukum Lex Generalis, 2024)
Judicial power is the main pillar in the judicial system that guarantees the upholding of law and justice. Judges as law enforcers have a strategic role in maintaining the integrity and public trust in judicial institutions. The independence and professionalism of judges must always be maintained so that they are not tainted by violations of the code of ethics and behavior that is contrary to judicial values. This study aims to analyze the role of the Judicial Commission in enforcing the code of ethics of judges with Judge DA case study, who was involved in drug abuse and other ethical violations. The research methods used are normative law and empirical juridical, with a focus on laws and regulations, Judicial Commission decisions, academic literature, and media coverage. The results of the study show that Judicial Commission has implemented a systematic supervisory mechanism, starting from verifying reports to imposing sanctions by the Judges' Honorary Council. The dishonorable dismissal of Judge DA reflects Judicial Commission's firmness in enforcing the code of ethics, but also highlights weaknesses in the system of selection, coaching, and supervision of judges. This case has an impact on the decline in the image of the judicial institution, but also becomes a momentum for improvement and evaluation of the supervision system to be more effective and preventive. This study concludes that strong supervision and cooperation between the Judicial Commission and other institutions, such as the Supreme Court, are very necessary to maintain the dignity of judges and increase public trust in the judiciary in Indonesia.